2016
DOI: 10.1007/s00404-016-4231-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the mechanism of hepatitis B virus father–infant transmission and pregnancy outcome

Abstract: HBV mRNA was found in abandoned IVF embryos of HBV-infected fathers, which confirmed that HBV could not only enter early cleavage embryos via sperm but also replicate in embryos, resulting in HBV father-infant transmission. HBV may interfere with embryonic development and thus affect pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
0
21
0
3
Order By: Relevance
“…In this scenario, some studies stated that HBV mRNA was identified in the embryos of HBV-infected fathers, implying the transcription and replication of HBV genes [10,11]. Nevertheless, while previous authors showed significantly lower pregnancy rate (PR) in HBV discordant couples likened to age-matched controls [12], other ones detected higher pregnancy, live birth and implantation rates (IRs) in HBV group [13].…”
Section: Introductionmentioning
confidence: 97%
“…In this scenario, some studies stated that HBV mRNA was identified in the embryos of HBV-infected fathers, implying the transcription and replication of HBV genes [10,11]. Nevertheless, while previous authors showed significantly lower pregnancy rate (PR) in HBV discordant couples likened to age-matched controls [12], other ones detected higher pregnancy, live birth and implantation rates (IRs) in HBV group [13].…”
Section: Introductionmentioning
confidence: 97%
“…Sperm with these chromosomal abnormalities can achieve normal fertilization and introduce these aberrations into the embryo, which may increase the risk of abortion, stillbirth, or birth defects [8]. In a recent clinical literature, HBV mRNA was found in abandoned IVF embryos of HBV-infected fathers, which confirmed that HBV could not only enter early cleavage embryos via sperm but also replicate in embryos, resulting in early abortion [47]. The aformentioned findings suggested that HBV may interfere with early embryonic development and thus affect pregnancy outcome.…”
Section: Discussionmentioning
confidence: 93%
“…One study showed that when men have an active HBV infection, using testicular sperm aspiration/ percutaneous epididymal sperm aspiration sperm may cause lower fertilization, a high miscarriage rate, and a lower live birth rate (14). Another study reported that IVF embryos of an HBV-positive father were successfully implanted, but early abortion occurred (24). Moreover, although ART dose not increase the risk for mother-to-child transmission of HBV, there is a degree of baseline risk through transplacental, intrapartum, and breastfeeding exposure that ART cannot offset.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the risk for father-to-child transmission of HBV during ART was not investigated in the present study. Previous studies have detected HBV DNA and RNA in embryos from couples with the husband alone being HBsAg-positive, suggesting that the sperm may act as a vector for the vertical transmission of HBV to the embryos, resulting in clinically significant father-to-child HBV transmission (7,24). However, there is evidence that the risk for fatherto-child HBV transmission in natural conception is limited (26).…”
Section: Discussionmentioning
confidence: 99%